Discovery of Selective Inhibitor Leads by Targeting an Allosteric Site in Insulin-Regulated Aminopeptidase - Ioannis Temponeras; Lykourgos Chiniadis; Athanasios Papakyriakou; Efstratios Stratikos (Pharmaceuticals, 2021)
Insulin-Regulated aminopeptidase (IRAP) is a zinc-dependent aminopeptidase with several important biological functions and is an emerging pharmaceutical target for cognitive enhancement and immune system regulation. Aiming to discover lead-like IRAP inhibitors with enhanced selectivity versus homologous enzymes, we targeted an allosteric site at the C-terminal domain pocket of IRAP. We compiled a library of 2.5 million commercially available compounds from the ZINC database, and performed molecular docking at the target pocket of IRAP and the corresponding pocket of the homologous endoplasmic reticulum aminopeptidase 1 (ERAP1). Of the top compounds that showed high selectivity, 305 were further analyzed by molecular dynamics simulations and free energy calculations, leading to the selection of 33 compounds for in vitro evaluation. Two orthogonal functional assays were employed: one using a small fluorogenic substrate and one following the degradation of oxytocin, a natural peptidic substrate of IRAP. In vitro evaluation suggested that several of the compounds tested can inhibit IRAP, but the inhibition profile was dependent on substrate size, consistent with the allosteric nature of the targeted site. Overall, our results describe several novel leads as IRAP inhibitors and suggest that the C-terminal domain pocket of IRAP is a promising target for developing highly selective IRAP inhibitors.